Large‐Scale and Wide‐Gamut Coloration at the Diffraction Limit in Flexible, Self‐Assembled Hierarchical Nanomaterials (Adv. Mater. 11/2022). Issue 11 (17th March 2022) - Li, Ning; Xiang, Fei; Elizarov, Maxim S.; Makarenko, Maxim; Lopez, Arturo B.; Getman, Fedor; Bonifazi, Marcella; Mazzone, Valerio; Fratalocchi, Andrea
Abstract : Structural Color A view of the large‐scale assembly of structural colors by different nanoresonators is shown, as described by Andrea Fratalocchi and co‐workers in article number 2108013 . Each nanoresonator is deformed in all dimensions, including the vertical axis, and supports competing mechanisms of scattering and resonant light–matter interactions that yield in high‐resolution, a complete gamut of colors even exceeding the red, green, and blue spectrum.